[Translated article] Adherence of Candida albicans and Malassezia Species to Skin Cells Induces Changes in the Expression of Genes Responsible for Heparan and Chondroitin Sulfate Chain Synthesis - H. Ordiales; F. Vázquez-López; M. Pevida; B. Vázquez-Losada; F. Vázquez; L.M. Quirós; C. Martín (Elsevier, 2022)
Superficial fungal infections are common in dermatology and are often caused by opportunistic species in the Candida and Malassezia genera. The aim of this study was to analyze changes in the expression of genes coding for enzymes involved in the biosynthesis of glycosaminoglycans (GAGs) chains following the adherence of Candida and Malassezia yeasts to skin cell lines. Gene expression was analyzed using reverse transcriptase-quantitative polymerase chain reaction assays. Interactions between the yeasts and the skin cells induced the following changes in genes involved in the biosynthesis of heparan sulfate and chondroitin sulfate: downregulation of CHPF in keratinocytes and downregulation of EXT1, EXT2, CHSY3, and CHPF in fibroblasts. Adherence to fibroblasts had an even greater effect on GAG biosynthetic enzymes, inducing the downregulation of 13 genes and the upregulation of two (CHST15 and CHST7). Interactions between yeasts and skin cells might affect the binding affinity of GAG chains, possibly changing their ability to function as receptors for pathogens and interfering with a key stage at the start of infection. Resumen: Las micosis superficiales son patologías prevalentes en dermatología, causadas frecuentemente por hongos oportunistas de los géneros Candida y Malassezia. El objetivo de este trabajo es analizar, mediante qRT-PCR, la existencia de alteraciones en la expresión génica de las enzimas biosintéticas de las cadenas de glicosaminoglicanos (GAGs) tras la adhesión de dichas levaduras a líneas celulares de piel. La interacción de C. albicans y Malassezia spp. produjo las siguientes modificaciones en genes implicados en la biosíntesis del heparán y condroitín sulfato: la subexpresión de CHPF en los queratinocitos y 4 subexpresiones (EXT1, EXT2, CHSY3 y CHPF) en los fibroblastos. Las enzimas implicadas en la modificación de las cadenas de dichos GAG se ven más alteradas en los fibroblastos, produciendo 13 subexpresiones y 2 sobreexpresiones (CHST15 y CHST7). Como consecuencia, la afinidad de las cadenas de GAGs por sus ligandos puede verse afectada, pudiendo alterar su papel como receptores de microorganismos, paso clave para el inicio de su proceso infeccioso.